Macrophages and neutrophils express IFNλs in granulomas from Mycobacterium tuberculosis-infected nonhuman primates - Talukdar, Priyanka; Junecko, Beth F.; Lane, Daniel S.; Maiello, Pauline; Mattila, Joshua T. (Frontiers in Immunology, 2022)
Granulomas are the hallmark of Mycobacterium tuberculosis (Mtb) infection. Cytokine-mediated signaling can modulate immune function; thus, understanding the cytokine milieu in granulomas is critical for understanding immunity in tuberculosis (TB). Interferons (IFNs) are important immune mediators in TB, and while type 1 and 2 IFNs have been extensively studied, less is known about type 3 IFNs (IFNs) in TB. To determine if IFNs are expressed in granulomas, which cells express them, and how granuloma microenvironments influence IFN expression, we investigated IFN1 and IFN4 expression in macaque lung granulomas. We identified IFN expression in granulomas, and IFN levels negatively correlated with bacteria load. Macrophages and neutrophils expressed IFN1 and IFN4, with neutrophils expressing higher levels of each protein. IFN expression varied in different granuloma microenvironments, with lymphocyte cuff macrophages expressing more IFN1 than epithelioid macrophages. IFN1 and IFN4 differed in their subcellular localization, with IFN4 predominantly localizing inside macrophage nuclei. IFNR1 was also expressed in granulomas, with intranuclear localization in some cells. Further investigation demonstrated that IFN signaling is driven in part by TLR2 ligation and was accompanied by nuclear translocation of IFNR1. Our data indicate that IFNs are part of the granuloma cytokine milieu that may influence myeloid cell function and immunity in TB.